2020
DOI: 10.3390/jcm9051284
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts on the Reno-Protective Effects of Phosphodiesterase 5 Inhibitors in Acute Kidney Injury: Systematic Search and Review

Abstract: Acute kidney injury (AKI) is associated with increased morbidity, prolonged hospitalization, and mortality, especially in high risk patients. Phosphodiesterase 5 inhibitors (PDE5Is), currently available as first-line therapy of erectile dysfunction in humans, have shown a beneficial potential of reno-protection through various reno-protective mechanisms. The aim of this work is to provide a comprehensive overview of the available literature on the reno-protective properties of PDE5Is in the various forms of AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 121 publications
0
34
0
1
Order By: Relevance
“…Other agents such as cardiotrophin-1 and antithrombin III, [ 53 , 54 ] exendin-4, [ 55 ] β-receptor antagonist, [ 56 , 57 ] phosphodiesterase-5 inhibitor, [ 58 61 ] an mTOR inhibitor, [ 62 ] exogenous sphingosylphosphorylcholine, [ 63 ] and sodium bicarbonate; [ 64 ] have been investigated in CIN models (Table 4 and Fig. 3 ).…”
Section: Interventions Targeting Ros For Cin Prevention: Evidence Fromentioning
confidence: 99%
“…Other agents such as cardiotrophin-1 and antithrombin III, [ 53 , 54 ] exendin-4, [ 55 ] β-receptor antagonist, [ 56 , 57 ] phosphodiesterase-5 inhibitor, [ 58 61 ] an mTOR inhibitor, [ 62 ] exogenous sphingosylphosphorylcholine, [ 63 ] and sodium bicarbonate; [ 64 ] have been investigated in CIN models (Table 4 and Fig. 3 ).…”
Section: Interventions Targeting Ros For Cin Prevention: Evidence Fromentioning
confidence: 99%
“…The reduction of nephrotoxic exposure is one of the effective tools already used in oncological patients [ 30 ]. The animal models suggest the possibility to prevent AKI with the use of phosphodiesterase-5 inhibitors prior to potentially nephrotoxic treatment [ 31 , 32 ]. Independent of the chosen strategy, the threat of renal injury should urge careful follow-up of the patient in order to avoid additional insults triggering irreversible damage to the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil is an orally administered phosphodiesterase type 5 (PDE5) inhibitor that permits corpus cavernosum smooth muscle to relax and potentiating erections during sexual stimulation (Langtry and Markham, 1999;Georgiadis et al, 2020;Iordache et al, 2020a). It is also reported that the sildenafil can inhibit the breakdown of cyclic guanosine monophosphate (cGMP) through binding at the phosphodiesterase binding site (Iordache et al, 2020b;Rogosnitzky et al, 2020).…”
Section: Sildenafilmentioning
confidence: 99%